Understanding the informal economy in practice: Evidence from Bosnia and Herzegovina - Nirha Efendic; Edin Pasovic; Adnan Efendic (e-Finanse: Financial Internet Quarterly, 2018)
This paper provides insights into the informal economy of Bosnia and Herzegovina (BiH), a post-conflict transition economy in the Western Balkan region aspiring to became part of the European Union. After the introductory section and literature review, we introduce the economic outlook of BiH and then provide evidence estimating the size of the informal economy, which is identified to be around 30% over the last couple of years. As the size of the informal economy is high and persistent, this implies that current policy approaches are not efficient in tackling this economic challenge. To understand how the informal economy operates in practice, we use data from two different surveys to assess tax morality, undeclared work and the structure of the participants in the informal economy. In the next section, we supplement the study with ethnographic insights. In particular, we identify how participants in the informal economy use it for different purposes and with different motives. This includes reliance on the informal economy as a survival strategy for households, as a way to supplement insufficient formal income, to compensate for economic insecurity, or to decrease costs of formal business by using 'envelope wage' practices, but equally importantly to overcome formal institutional rigidities linked to current contradictory laws.
Keywords: O17; 330; informal economy; formal institutions; informal institutions; undeclared work; Bosnia and Herzegovina